Proteins:Vol-1. From Analytics to Structural Genomics - Meyers, Robert Allen;Ed (Wiley-VCH, 2007)
3 Nobel laureates contribute to this invaluable collection of high-quality articles, extracted from the much-praised R.A. Meyer-s Encyclopedia. With sections on Structure, Modeling, Expression, Analysis and others, this book covers a wide range of topics in protein research.